High mass absorption efficiency of carbonaceous aerosols during the biomass burning season in Chiang Mai of northern Thailand - Jun Tao (2020)
© 2020 Elsevier Ltd Southeast Asia is one of the major regions of biomass burning in the world. To investigate the light absorption properties of carbonaceous aerosols produced from biomass burning, mass concentrations of PM2.5 and its major chemical compositions were obtained by filter sampling, and aerosol absorption coefficient (bap) at 370 nm (bap-370nm) and at 880 nm (bap-880nm) were synchronously determined for the sampled filters using a transmissometer in urban Chiang Mai of Northern Thailand during the dry season in 2019. On campaign average, the reconstructed PM2.5 mass from the measured chemical components accounted for 99% of the measured PM2.5 mass, in which organic matters (OM) accounted for 64 ± 10%. Hardwood burning was identified as the dominant source of carbonaceous aerosols. The measured aerosol absorption Ångström exponent (AAE) at 370–880 nm (AAE370–880nm) was 1.71 ± 0.24. Mass absorption efficiency (MAE) of elemental carbon (EC) and organic carbon (OC) was estimated using a multiple linear regression model between bap and mass concentrations of EC and OC, resulting in campaign-average values of 8.11 m2 g−1 and 0.24 m2 g−1 at 880 nm and 21.06 m2 g−1 and 2.57 m2 g−1 at 370 nm, respectively, which were evidently larger than those in other cities worldwide. The contributions of EC to bap in 370–880 nm spectrum region ranged from 49 ± 5% to 79 ± 3%, and those of OC ranged from 51 ± 5% to 21 ± 3%. Results from this study suggested a potentially significant impact of carbonaceous aerosols on direct radiative forcings in the dry season over Southeast Asia and downwind regions.